Frankie vs the Cowboy's Crew - Lampard, Frank (Little, Brown Books for Young Readers London, 2015)
Frankie and his team love playing football. There's always time for a game. And now that they have their magical football they're playing against teams they never imagined! When they're transported back into the Wild West, Frankie's team will have to go head-to-head with some crabby cowboys. Will they be able to win the penalty shoot out at high noon?